Perlindungan Konsumen terhadap Hak Memperoleh Informasi dalam Pembatalan Konser Secara Sepihak (Studi Kasus Konser K-pop We all are one) - Zidan Azayda Sabil; Indah Parmitasari (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The problem in this study is about how consumer protection in terms of obtaining the right to information in the case of unilateral cancellation of concerts and how the responsibility of promoters to ticket buyers due to unilaterally canceled concerts (K-pop concert "We all are one"). The research method used is a type of normative juridical legal research using the statue approach, case approach, and conceptual approach using primary, secondary, and tertiary legal materials. Data collection techniques are carried out through literature studies, which involve collecting legal materials that are analyzed, reviewed, and studied through journals, legal research results, and various official documents such as laws and regulations using qualitative descriptive analysis methods. The result of this study is that consumer protection in obtaining the right to information has not fully run in accordance with Article 4 letter c and Article 7 letter b of consumer protection law and the responsibility of the promoter has not fully run in accordance with Article 19 of consumer protection law where the promoter must provide compensation or compensation.